Optimizing the reproductive performance of clownfish Amphiprion percula: Effects of artificial substrates on spawning, fertilization, and hatchability in captive breeding - Iftahuddin, Iftahuddin; Muliani, Muliani; Zulfikar, Zulfikar (Journal of Marine Studies, 2025)
The increasing demand for marine ornamental fish, particularly Amphiprion percula, has raised concerns about sustainability due to the heavy reliance on wild-caught specimens. Captive breeding programs offer a viable alternative; however, reproductive success varies significantly depending on the artificial substrates used. This study examines the effects of different substrate types on spawning duration, fertilization rate, and egg hatchability in A. percula under controlled aquaculture conditions. A completely randomized design was implemented, testing four substrate types”cobek (earthenware, control), PVC pipes, ceramic pieces, and asbestos sheets”with three replicates each. Broodstock were maintained in optimized water quality conditions, with regular monitoring of feeding regimes and spawning behavior. The results demonstrated that substrate type significantly influenced reproductive parameters. The shortest spawning interval was observed in the cobek treatment (7 days), while the longest was recorded in the asbestos treatment (32.67 days). Fertilization rates ranged from 96.67% in the cobek treatment to 93.42% in the PVC pipe treatment. Notably, the hatchability of fertilized eggs remained consistently at 100% across all treatments, suggesting that artificial substrates do not compromise embryonic development. Water quality parameters were maintained within optimal ranges throughout the experiment, ensuring a stable rearing environment. This research contributes to the improvement of captive breeding practices, reducing dependency on wild populations and supporting the sustainable trade of marine ornamental fish. Future studies should explore additional factors influencing breeding success, including environmental cues and broodstock conditioning, to further refine aquaculture methodologies.